The Business of Software Don't Bring Me a Good Idea. - Armour, Phillip G. (Communications of the ACM, 2011)
The article examines how employees may present opportunities for revenue growth, such as new products and new customers, to managers whom they are attempting to convince to buy in to software quality and process change initiatives. The author discusses the need for obtaining sponsorship for software development process changes, for collecting data and instrumenting complex systems to manage predictive analytics, and for testing these predictive systems. Quotes are presented from power production firm SmartSignal chief executive officer Jim Gagnard, as well as software company Microsoft’s Relationship Experience Division general manager Jason Kalich.